THE LEVEL OF ANTIVIRAL ANTIBODIES AND INDEXES OF LOCAL IMMUNITY INTHE DYNAMICS OF THE TREATMENT OF CHILDREN WITH GLOMERULONEPHRITIS IN THE PRESENCE OF HERPESVIRAL INFECTION - Kruglikov, V.; BagdasarovaІ.; KruglikovaІ.; KornilinaЕ. (Ukrainian Journal of Nephrology and Dialysis, 2016)
The aim of the work was to study of indicators characterizing the state of local immunity, tension of specific immunity in children with variousforms of glomerulonephritis (GN) by presence of herpesviral infection (HVI) in the dynamics oftreatment using antiviral therapy. Materials and methods. A quantitative assessment of the content of slgA, SLPI, MCP-1 and IL-8 in the urine of 37 patients with glomerulonephritis and 10 apparently healthy individuals was conducted. In serum of blood were determined specific IgGand IgMantibodies to HSV, CMVand EBV. Results. The most common HVI was caused by EBV (78,4%) in children with GN. The use of antiviral therapy helped to reduce the level ofspecific IgGin the blood ofchildren with GN in 86.1%of the active (reactivated) HVIand in 38,9% - below the diagnostically significant parameters. Inclusion of antiviral agents to standard therapy of GNpatients in the presence of HVI can reduce the level of MCP-1 and IL-8 in the urine, which indicates the reduction of inflammatory processes in the kidney. There was noted an increase in urine the slgA and SLPI concentrations due to antiviral treatment, but these changes were within the physiological norm, in contrast to patients who had received only standard therapy, which were determined by considerably exceeding the norm value. Conclusion. Appointment of antiviral therapy leads to a transitionfrom active infection to the latent stage of theflow, which improves the clinical condition.